1970
DOI: 10.1111/j.1532-5415.1970.tb02829.x
|View full text |Cite
|
Sign up to set email alerts
|

Speculations on Vascular Changes With Age

Abstract: Several extracardiac age changes may affect cardiovascular efficiency. Extracellular fluid and blood volume are relatively increased with age. The loss of aortic elasticity results in a rise in systolic pressure when work produces increases in cardiac output. The vascular rigidity further consumes energy by loss of the propulsive effect of elastic recoil. Finally, peripheral resistance increases due to arteriolar constriction; this appears to be under reversible physiologic control. The sum of these normal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Such activities depend on the integrated efforts of the lungs, heart, and circulation to deliver oxygen to metabolically active muscles [36]. In adults over the age of 35 years, maximum oxygen uptake (V · O2max), the most reliable indicator of endurance performance and cardiovascular fitness, declines at a rate of 0.5-1.0% annually [37,38]. This diminution may be reduced with physical activity and is increased in sedentary people; it was shown to be less than 0.1% in master athletes [39].…”
Section: Requirements Of Aerobic Performance In Elderly Mountaineersmentioning
confidence: 99%
“…Such activities depend on the integrated efforts of the lungs, heart, and circulation to deliver oxygen to metabolically active muscles [36]. In adults over the age of 35 years, maximum oxygen uptake (V · O2max), the most reliable indicator of endurance performance and cardiovascular fitness, declines at a rate of 0.5-1.0% annually [37,38]. This diminution may be reduced with physical activity and is increased in sedentary people; it was shown to be less than 0.1% in master athletes [39].…”
Section: Requirements Of Aerobic Performance In Elderly Mountaineersmentioning
confidence: 99%
“…Though specific binding studies have not been conducted in elderly patients, the observation that plasma albumin decreases with increasing age (44, 45) implies that the amount of bound drug would be reduced with age. With regard to peripheral blood flow, it has been demonstrated that a depressed cardiac output in older patients is redistributed in favor of the cerebral and coronary circulations at the expense of flow to the kidney and liver (30, 46).…”
Section: Drug Distributionmentioning
confidence: 99%
“…The primary intra-or extracellular source of calcium for the contractile response appears to depend on the contractile agonist [Hiraoka et al, 1968;Hudgins and Weiss, 1968;Greenberg et al, 1973]. Since multiple vascular changes [Goldman, 1970] occur with age, the possibility exists that the source of calcium required for vas cular contraction may also vary with age.…”
Section: Introductionmentioning
confidence: 99%